Effect of strain rate and fibre rotation on the in-plane shear response of ±45° laminates in tension and compression tests. (27th October 2016) - Cui, Hao; Thomson, Daniel; Pellegrino, Antonio; Wiegand, Jens; Petrinic, Nik
Abstract: This work focuses on the effect of strain rate and fibre rotation on the in-plane shear properties of composite laminates. The effect of fibre rotation on the measured shear properties, was for the first time experimentally quantified with the comparison between compression and tension tests of the ±45° laminate samples. Significant increase of shear strength and decrease of final failure strain was observed with the increase in strain rate from 5e-4 1/s to 1300 1/s. The nonlinear shear model was developed to simulate the large deformation process, in which the fibre orientation was updated as a function of the in-plane shear strain. The results of this investigation should motivate the updating of procedures for experimental characterization as well as analytical and numerical modelling of in-plane shear response of laminates.